Adaptive algorithms for automated intruder detection in surveillance networks - Ahmed, Tarem; Ahmed, Supriyo Sabbir; Pathan, Al-Sakib Khan (© 2014 Institute of Electrical and Electronics Engineers Inc., 2016)
This conference paper was presented in the 3rd International Conference on Advances in Computing, Communications and Informatics, ICACCI 2014; Delhi; India; 24 September 2014 through 27 September 2014 [© 2014 Institute of Electrical and Electronics Engineers Inc.] The conference paper's definite version is available at: http:// 10.1109/ICACCI.2014.6968617